Penggunaan Obat Kumur Larutan Lidah Buaya (Aloe vera) pada Penyembuhan Luka Pasca Scaling - Mirawati, Ellis; Thioritz, Ernie; Haryuasrani (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2023)
The scaling action often puts pressure on the gums, which causes sores with symptoms such as pain, swollen gums (gingivitis), a bright red color, sensitivity, and bleeding easily. After scaling, the patient will be given mouthwash so that the gums are healthy again. Mouthwashes containing anti-microbial substances can be classified into two namely the active substances derived from plants and those made from chemicals. However, long-term use of chemical mouthwashes can result in a number of side effects. Long term use of chemical mouthwashes can result in a number of side effects and is expensive, so the use of herbal inrediets is an alternative in oral medicine. This study aims to determine the effect of gargling Aloe vera solution to accelerate wound healing after scaling. This study used a descriptive quantitative. The number of samples is 30 people, 15 people gargling with Aloe vera solution and 15 people gargling with mineral water. The results showed that in all patients who were given aloe vera intervention, the wound healing process was faster than that of those who rinsed using plain water. Keywords : Aloe vera; wound; scaling